Anatomía de la madera de Buddleja L. (Buddlejaceae): análisis fenético - Aguilar-Rodríguez, Silvia; Terrazas, Teresa (Instituto de Ecología, A.C., 2016)
Buddleja L. comprises nearly 100 species with pantropical distribution, varying from small shrubs to trees 20 to 30 meters high and few lianas. In this study wood anatomical characteristics of Buddleja are presented based on the study of 41 species, of those 10 are described for the first time, and 15 synthesized from the literature. Also the wood features for 41 species of the genus were analized through a phenetic analysis. The genus showed ring to diffuse porosity, simple perforation plates, alternate intervascular pits, and helical thickenings in vessel elements and vascular tracheids; libriform fibers, with septa in some species; axial parenchyma scanty or rare; heterogeneous rays type IIB and 35% of the species contain prismatic crystals of different size in their ray cells. Phenetic analysis showed that several species are anatomically identical. However, most species conformed two large groups based on qualitative and quantitative wood features. Moreover, other species are distinctive based on the presence of unique qualitative characters. Finally, some taxonomic considerations on Buddleja position within the Scrophulariales order are discussed.